2012
DOI: 10.1007/s40262-012-0025-6
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Losmapimod in Healthy Subjects and Patients with Rheumatoid Arthritis and Chronic Obstructive Pulmonary Diseases

Abstract: The population pharmacokinetic model described in this work well characterized the pharmacokinetic profile of losmapimod following administration of a single oral dose and repeated oral doses in healthy subjects and patients with RA and COPD. Although sex, bodyweight and age were significant factors influencing some pharmacokinetic parameters of losmapimod, the relatively small magnitude of the effect did not result in concerns for dose adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The mortality rate of RA in worldwide populations varies from 0.01-0.05%, and prevalence rate is 0.18-1.07% (3). RA is also an impactful disease, resulting in labor loss and disability in China (2).…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of RA in worldwide populations varies from 0.01-0.05%, and prevalence rate is 0.18-1.07% (3). RA is also an impactful disease, resulting in labor loss and disability in China (2).…”
Section: Introductionmentioning
confidence: 99%
“…Losmapimod ( Figure 1A) is a potent p38 MAPK inhibitor currently being developed by GlaxoSmithKline for the treatment of ACS and chronic obstructive pulmonary disease and is also under investigation for use in the treatment of other conditions involving inflammation, including rheumatoid arthritis and neuropathic pain. [10][11][12] As ethnicity may potentially be associated with differences in drug response, it is important to study drugs in subjects from a variety of ethnic backgrounds. Therefore, this study investigated the potential effect of ethnicity on the absorption, distribution, metabolism, and elimination of losmapimod in a group of healthy Japanese subjects.…”
mentioning
confidence: 99%
“…Inhibition of p38 MAPK has the potential to provide clinical benefit in patients presenting with MI through inhibition of inflammation, thereby modulating a mechanism of the disease that has not been addressed fully by currently available treatments. Losmapimod (Figure A) is a potent p38 MAPK inhibitor currently being developed by GlaxoSmithKline for the treatment of ACS and chronic obstructive pulmonary disease and is also under investigation for use in the treatment of other conditions involving inflammation, including rheumatoid arthritis and neuropathic pain …”
mentioning
confidence: 99%
“… 21 Another population PK meta-analysis that included data from three studies (30 healthy volunteers, 23 subjects with rheumatoid arthritis, and 24 subjects with COPD) showed that although some variation by age, sex, and body weight may be expected in losmapimod PK measures, there was no indication for dose adjustment according to these parameters. 28 …”
Section: Phase I Clinical Studies Of Losmapimodmentioning
confidence: 99%